The first record of Sarcophaga ruficornis Fabricius, 1794 (Diptera: Sarcophagidae) from Egypt: flesh flies of medical interest - Abu El-Hassan, Gawhara M. M.; Abo El-Ela, Reham H.; Sawaby, Rabab; El-Hamouly, Hayam; El-Sawaf, Bahira M.; Ghallab, Enas H. (Entomological Communications, 2023)
In this study, Sarcophaga ruficornis Fabricius, 1794 (Diptera: Sarcophagidae) is recorded for the first time from the Egyptian fauna. The identification was confirmed using integrative approach of morphology and molecular technique.